Guía de laboratorío del brazo robot scorbot-er 4u - Arellano Arroba, Camilo David (2009)
This material is an educational tool for training the robot arm Scorbot-ER 4u and accessories. The first part sets out the mechanical and physical limitations of the robot arm, identifies the axes here that has the robot arm movement. After, defining the physical and electrical characteristics of the Controller-USB, electronic equipment required to manipulate the arm and accessories. Is then specify six Scorbot robotic system accessories. In the next section presents the programming environment, which is the software required to program the system. A major issue is considered below consists of security. That is, precautionary measures are considered necessary to prevent accidents, protecting the operator and the robotic system Scorbot. Finally, it was specified nine areas of laboratory practice for the arm Scorbot-ER 4u robot and its accessories, whose themes are: "Introduction to the programming environment, Movements of the robot arm through commands, Coordinate system, Linear basis of 1 meter, Table of experiments, Conveyor belt, Rotary table, Input and output analog Controller-USB, and Pneumatic system.”